Genomic investigation of Salmonella enterica Serovar Welikade from a pediatric diarrhea case first time in Shanghai, China - Shen, Yinfang; Zhou, Yibin; Gong, Jingyu; Li, Gang; Liu, Yue; Xu, Xuebin; Chen, Mingliang (BMC genomics, 2024)
Salmonella, an important foodborne pathogen, was estimated to be responsible for 95.1 million cases and 50,771 deaths worldwide. Sixteen serovars were responsible for approximately 80% of Salmonella infections in humans in China, and infections caused by a few uncommon serovars have been reported in recent years, though not with S. Welikade. This study reports the first clinical case caused by S. Welikade in China and places Chinese S. Welikade isolates in the context of global isolates via genomic analysis. For comparison, S. Welikade isolates were also screened in the Chinese Local Surveillance System for Salmonella (CLSSS). The minimum inhibitory concentrations (MICs) of 28 antimicrobial agents were determined using the broth microdilution method. The isolates were sequenced on an Illumina platform to identify antimicrobial resistance genes, virulence genes, and phylogenetic relationships. The S. Welikade isolate (Sal097) was isolated from a two-year-old boy with acute gastroenteritis in 2021. Along with the other two isolates found in CLSSS, the three Chinese isolates were susceptible to all the examined antimicrobial agents, and their sequence types (STs) were ST5123 (n = 2) and ST3774 (n = 1). Single nucleotide polymorphism (SNP)-based phylogenetic analysis revealed that global S. Welikade strains can be divided into four groups, and these three Chinese isolates were assigned to B (n = 2; Sal097 and XXB1016) and C (n = 1; XXB700). In Group B, the two Chinese ST5123 isolates were closely clustered with three UK ST5123 isolates. In Group C, the Chinese isolate was closely related to the other 12 ST3774 isolates. The number of virulence genes in the S. Welikade isolates ranged from 59 to 152. The galF gene was only present in Group A, the pipB2 gene was only absent from Group A, the avrA gene was only absent from Group B, and the allB, sseK1, sspH2, STM0287, and tlde1 were found only within Group C and D isolates. There were 15 loci unique to the Sal097 isolate. This study is the first to characterize and investigate clinical S. Welikade isolates in China. Responsible for a pediatric case of gastroenteritis in 2021, the clinical isolate harbored no antimicrobial resistance and belonged to phylogenetic Group B of global S. Welikade genomes.